PENGALIHAN HAK SEWA TANAH PERSPEKTIF FIQIH MU’AMALAH DAN HUKUM POSITIF DI INDONESIA - Muh Soleh Aminullah (Indonesian Journal of Law and Islamic Law (IJLIL), 2021)
Leasing is an agreement between one party that undertakes and binds itself to hand over the benefits of an item to another party for a certain period of time followed by payment as a reward. Along the way, the practice of renting does not always work as it should. Like the leasing that occurred in Jatimulyo Village, where one party could transfer the lease rights to another party when the lease was in progress. The method used in this study uses descriptive qualitative with short interviews with certain parties. The results of the study are: Fiqih Mu'amalah perspective on the practice of transferring lease rights that is carried out is penalized null (fasakh), because the transfer made is not in accordance with the provisions of the stipulated syara ', and there is no authority of the tenant for the transfer made. Meanwhile, the positive legal perspective in Indonesia on the practice of transferring land lease rights to third parties is an activity that is not allowed. This is in accordance with Article 1559 of the Civil Code, which does not require the lessee to release his lease to another party unless there is approval from the land owner, as well as a statement that the transfer may be made. Likewise with Article 310 KHES that tenants are not allowed to rent goods (land) that are leased to other parties except with the permission of the renting party.